Analysis of the Impact of Tourism on the Community Economy in the Colorful Village of Parapat - Sinaga, Grace; Rahel, Gracia; Manik, Yohana; Ramadhan, Ikhlas (Journal of Tourism Economics and Policy, 2026)
This study aims to analyze the impact of tourism development on increasing community income in Kampung Warna Warni Parapat and identify factors that influence this impact. The method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results of the study indicate that tourism development in Kampung Warna Warni has a significant economic impact on the local community, as seen from the increase in the number of tourists, the opening of micro-business opportunities, and community involvement in homestay management and digital promotion. Factors that influence this impact include active community participation in tourism activities, the development of community-based homestays, optimizing the use of social media, infrastructure improvements, strengthening entrepreneurship, and increasing local economic turnover. All of these factors contribute to improving the welfare of the local community. However, in addition to positive impacts, challenges also arise such as increasing waste volume and the risk of environmental pollution that need to be anticipated with appropriate strategies. Therefore, a sustainable tourism development approach based on local wisdom is essential to maintain the balance of economic, social, and environmental aspects in the tourist village.